Analisis Kemampuan Literasi Numerasi Siswa SMP Ditinjau dari Adversity Quotient dan Jenis Kelamin - Syamsyiah, Zahra Maya; Handayani, Isnaini (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
The government's new policy of changing the National Examination (UN) to the National Assessment (AN), requires all students in Indonesia to have competence, one of which is numeracy literacy. In describing this numeracy literacy ability, it can be viewed from all aspects, one of which is: Adversity Quotient (AQ). This study aims to describe the differences in the numeracy abilities of junior high school students in terms of the Adversity Quotient between male and female students. This research is a descriptive qualitative research, with a research subject of 6 eighth-grade students of one of the State Junior High Schools in Depok. The instruments used were test and non-test instruments, namely written tests, questionnaires, and interviews. This study uses data analysis techniques, namely data reduction, data presentation, and conclusion. The research findings indicate that both male and female climber students demonstrate high numeracy literacy skills by fulfilling all the indicators. Camper students, show moderate numeracy literacy skills, with males fulfilling two indicators and females fulfilling one indicator. As for quitter students, they exhibit low numeracy literacy skills as they do not fulfill any of the indicators. The difference between men and women of each type is only in the completion steps and explaining the reasons for each answer they choose.